KETAHANAN SOSIAL MASYARA.KAT DALAM PERSPEKTIF AGAMA DAN ETNIS (Studi Kasus di Kelurahan MARIO dan LETTE, Kecamatan Mariso - Kota Makasar) - Abu Hanifah; Hemat Sitepu (Puslitbangkesos Kementerian Sosial RI, 2010)
The research is descriptive qualitative that aimed to know: (1) understanding of people of multi religion and ethnic, (2) togetherness of community that consists of varies religion and ethnic, (3) related factors of togetherness. Main data has collected by interview and FGD, while secondary data has been taken from Makassar on Numbers and profiles of two villages that as target of this research. The research found the community has understood of the differences of religion and ethnic that brought varies of cultures that may fragile to be conflict. However, by sense of awareness of variety then the conflict can be avoided. By thisawareness, the community possibly to work together through social organizations, both facilitated by government and local wisdom. The support of togetherness has triggered by social awareness that average of their education are quite high and the well being of social organization that as media of togetherness. On the other hand, both two villages have not protect yet of the fragile community, poor, and other social problems. In order to enhance social resilience and social welfare, has recommended the Social Office of Makassar payattention for poor people by giving economic-productive aids, and especially the Ministry of Social Affairs may be conducting Social Empowerment program.